The bookshop at water's end - Henry, Patti Callahan (Berkley, 2017)
"Bonny Blankenship's most treasured memories are of idyllic summers spent in Watersend, South Carolina, with her best friend Lainey McKay. Amid the sand dunes and oak trees draped with Spanish moss, they swam and wished for happy-ever-afters, then escaped to the local bookshop to read and whisper in the glorious cool silence. Until the night that changed everything, the night that Lainey's mother disappeared. Now, in her early fifties, Bonny is desperate to clear her head after a tragic mistake threatens her career as an emergency room doctor, and her marriage crumbles around her. With her troubled teenage daughter, Piper, in tow, she goes back to the beloved river house, where she is soon joined by Lainey and her two young children. During lazy summer days and magical nights, they reunite with bookshop owner Mimi, who is tangled with the past and its mysteries. As the three women cling to a fragile peace, buried secrets and long ago loves return like the tide"--